Alteration in NMDA receptor subunit mRNA expression in vulnerable and resistant regions of in vitro ischemic rat hippocampal slices. - Small, D; Poulter, M; Buchan, A; Morley, P (1997)
Brain insults, including cerebral ischemia, can alter glutamate receptor subunit expression in vulnerable neurons. Understanding these post-ischemic changes in glutamate receptors could enhance our ability to identify specific, novel neuroprotective compounds. Reverse transcription-polymerase chain reaction (RT-PCR) amplification was used to quantify the altered expression of the N-methyl-D-aspartate (NMDA) NR2A, NR2B and NR2C subunits relative to one another in rat hippocampal slices in resistant and vulnerable regions following in vitro oxygen-glucose deprivation. Ninety minutes after re-oxygenation and return to 10 mM glucose, there was a significant increase in the expression of NR2C relative to NR2B and NR2A in the slice as a whole, as well as in the selectively vulnerable CA1 region and the resistant CA3 and dentate gyrus regions.